Outcome-Driven Business Architecture : Synergizing Strategies and Intelligence with Architecture - Tiwary, Amit; Unhelkar, Bhuvan; Taylor and Francis (Boca Raton, FL : Auerbach Publications, an imprint of Taylor and Francis, 2018)
This book discusses business architecture as a basis for aligning efforts with outcomes. It views BA as complementary to enterprise architecture, where the focus of technological initiatives and inventories is to understand and improve business organization, business direction, and business decision-making. This book provides a practical, long-term view on BA. Based on the authors' consulting experience and industrial research, the material in this book is a valuable addition to the thought processes around BA and EA. The lead author has direct and practical experience with large clients in applying APQC capability framework for undertaking multiple enterprise-wide capability assessments.
List of Figures -- List of Tables -- Acknowledgments -- Foreword -- Preface -- Authors --Section A CONCEPTS AND ODBA FRAMEWORK -- 1 Business Strategies and Outcome-Driven Business Architecture -- 2 Developing Business Architecture ICapabilities and Challenges -- 3 Developing Business ArchitectureII -- 4 Building and Assessing Business CapabilitiesI -- 5 Implementing Business CapabilitiesII -- 6 Metrics and Measurements with Outcome-Driven Business Architecture -- 7 Governance, Risk, and Compliance and Quality --Section B PRACTICE AND TOOLS -- 8 Establishing and Managing the Business Architecture Practice -- 9 ODBA, Big Data, and a Functioning Agile Organization --Section C CASE STUDIES -- 10 Business Architecture and Capability Case Study 1Manufacturing Industry -- 11 ODBA and Capability-Building Case Study 2Energy Market -- 12 Business Architecture and Capability Case Study 3Government Services --Bibliography -- Index.
Includes bibliographical references and index.
Also available in print format.
Keywords: COMPUTERS / Information Technology; Strategic planning; Management; Business enterprises; Electronic books